Revolutionary routines : the habits of social transformation - Pedwell, Carolyn (Outspoken (McGill-Queen's University Press), 2021)
"Although we tend to associate social transformation with major events, historical turning points, or revolutionary upheaval, Revolutionary Routines argues that seemingly minor everyday habits are the key to meaningful change. Through its account of influential socio-political processes--such as the resurgence of fascism and white supremacy, the crafting of new technologies of governance, and the operation of digital media and algorithms--this book rethinks not only how change works, but also what counts as change. Drawing examples from the affective politics of Trumpism and Brexit, nudge theory and behaviour change, social media and the international refugee crisis, and the networked activism of Occupy and Black Lives Matter, Carolyn Pedwell argues that minor gestures may be as significant as major happenings, revealing the powerful potential in our ability to remake shared habits and imaginatively reinhabit everyday life. Revolutionary Routines offers a new understanding of the logics of habit and the nature of social change, power, and progressive politics, illustrating diverse forms of consciousness and co-operation through which political solidarities might take shape."--